A bio-based click reaction leading to the dihydropyridazinone platform for nitrogen-containing scaffolds. Issue 7 (15th March 2023) - Chen, Jia-Yue; Huang, Yao-Bing; Hu, Bin; Li, Ke-Ming; Zhang, Ji-Long; Zhang, Xuan; Yan, Xia-Yun; Lu, Qiang
Abstract : The first biomass-based click reaction is reported to synthesize DHMP from biomass and through DHMP transformation. Abstract : N-containing chemicals are increasingly utilized as building blocks in the synthesis of medicines, pesticides, polymers, and other functional materials. However, efficiently accessing N-containing chemicals from biomass and their platform compounds remains a pivotal challenge. We here report the first biomass-based click reaction to synthesize a nitrogen-containing compound, 4, 5-dihydro-6-methylpyridazin-3(2 H )-one (DHMP), from biomass-derived levulinic acid (LA) and hydrazine hydrate. The reaction proceeded in water under a catalyst-free condition and achieved a quantitative product yield at room temperature in a few minutes, fulfilling the criteria of a click reaction. Furthermore, DHMP was selectively transformed into a range of bio-based N-containing chemicals, namely pyrrolidone, pyridazinone, and alkyl pyridazinone, through different catalytic approaches, demonstrating the feasibility of using DHMP as a N platform. The current work opens up a new realm in biomass utilization and also adds a new category to the current bio-based N-containing chemical families.